Analisis Sistem Logistik Gudang Terhadap Efektivitas Distribusi dan Akurasi Pengelolaan Stok di PT. Sari Warna Asli Garment Solo - Rizki Ardiasa Kusuma Dewa; Sulida Erliyana; Tini Utami (Politeknik bumi Akpelni, 2026)
The warehouse logistics system is an integral part of supply chain management, serving to ensure availability in the right quantities and at the right time.This study aims to analyze the role of the warehouse logistics system in distribution effectiveness and stock accuracy at PT. Sari Warna Asli Garment Solo. The approach used is quantitative associative. Data were obtained by distributing questionnaires to 100 respondents involved in the company's logistics and operational activities. The data analysis technique used was Multivariate Analysis of Variance (MANOVA) to simultaneously test the role of independent variables on two dependent variables. Data processing was performed using SPSS version 22. The analysis results indicate that the warehouse logistics system plays a significant role in distribution effectiveness and stock management accuracy, as evidenced by the results of univariate tests with a significance value of 0.000 (Sig. <0.05) and MANOVA tests with a significance value of 0.000 (Sig. <0.05). Ho is rejected and Ha is accepted. These findings confirm that the warehouse logistics system is a crucial factor in dan persaingan bisnis industri yang semakin ketat, efektivitas distribusi dan akurasi pengelolaan stok menjadi faktor kunci dalam keberhasilan operasional perusahaan supporting distribution effectiveness and stock management accuracy at the company.